FAKTOR-FAKTOR YANG MEMPENGARUHI WORD OF MOUTH PADA NASABAH BANK - DEWI KARLINA; DENNY SEPTA HARYANTI (Media Bisnis, 2021)
The purpose of this study is to know how the influence of Service Quality, Perceived Value, and Convenience to Word of Mouth in Mandiri Syariah Bank Jakarta Kedoya Branch and Jakarta Tanjung Duren Branch.The research design used in descriptive research and causality research. The sampling used in this research is nonprobability sampling by purposive sampling methods and will require 152 respondents. The respondents must be the customer in Mandiri Syariah Bank Jakarta Kedoya Branch and Jakarta Tanjung Duren Branch. The research data is processed with IBM Statistic 23 as a tool.The result showed that service quality have an impact to word of mouth. Perceived value have no impact to word of mouth. Convenience have an impact to word of mouth.